Animal-assisted Wellness Center - Sebastian, Maxine Selina C. (College of Architecture, University of the Philippines Diliman, 2019)
The Animal-assisted Wellness Center will be the first attempt at combining an animal-assisted interventions center, a mental health outpatient facility, veterinary clinic, and animal rehabilitation center and shelter into one cohesive building type in the Philippines. This project will be based on the philosophy of mutual healing, thus the center's main goal is to help people who are suffering from mental illness and simultaneously alleviate the problem of homeless cats and retired working dogs by providing them with more opportunities for finding homes and opportunities to receive extra love and attention from patients along the way. The center will cater to the outpatient mental health needs of the community with traditional psychological therapy and treatments as well as complementary holistic wellness treatments including therapy and treatments as well as complementary holistic wellness treatments including therapy using the arts, movement, and with the special addition of animal-assisted therapy. The animal shelter shall have the aim rabbits, as well as retired working dogs. This goal will be aided by the rescue animal's participation in the animal therapy programs and pet cafe through added exposure and awareness. The animal therapy center shall specialized in training and screening all prospective therapy animals. Therapy animals shall initially be limited to cats, dogs, rabbits and horses. Lastly, in addition to catering to the health needs of all the animals on site, the veterinary clinic shall offer grooming services and affordable spaying and neutering services.